Microbial metabolic interaction in fermentation ecosystem and cooperation in flavor compounds formation of Chinese cereal vinegar - Yanfang Wu; Jing Liu; Dantong Liu; Mengle Xia; Jia Song; Kai Liang; Chaochun Li; Yu Zheng; Min Wang (Food Science and Human Wellness)
Shanxi aged vinegar (SAV) is a famous cereal vinegar in China, which is produced through a solid-state fermentation where diverse microbes spontaneously and complex interactions occur. Here, combined with the metatranscriptomics, the microbial co-occurrence network was constructed, indicating that Lactobacillus, Acetobacter and Pediococcus are the most critical genera to maintain the fermentation stability. Based on an extensive collection of 264 relevant literatures, a transport network containing 2271 reactions between microorganisms and compounds was constructed, showing that glucose (84% of all species), fructose (67%) and maltose (67%) are the most frequently utilized substrates while lactic acid (64%), acetic acid (45%) are the most frequently occurring metabolites. Specifically, the metabolic influence of species pairs was calculated using a mathematical calculation model and the metabolic influence network was constructed. The topology properties analysis found that Lactobacillus was the key role with robust metabolic control of vinegar fermentation ecosystem and acetic acid and lactic acid were the main metabolites with feedback regulation in microbial metabolism of SAV. Furthermore, systematic coordination of positive and negative impacts was proved to be inevitable to form flavor compounds and maintain a natural microbial ecosystem. This study provides a new perspective for understanding microbial interactions in fermented food.